Transcriptome Analysis Reveals Photoperiod-Associated Genes Expressed in Rice Anthers - Sun, Shiyu; Wang, Duoxiang; Li, Jingbin; Lei, Yaqi; Li, Gang; Cai, WenGuo; Zhao, Xiangxiang; Liang, Wanqi; Zhang, Dabing (Frontiers in Plant Science, 2021)
Environmental conditions, such as photoperiod and temperature, can affect male fertility in plants. While this feature is heavily exploited in rice to generate male-sterile lines for hybrid breeding, the underlying molecular mechanisms remain largely unknown. In this study, we use a transcriptomics approach to identify key genes and regulatory networks affecting pollen maturation in rice anthers in response to different day lengths. A total of 11,726 differentially expressed genes (DEGs) were revealed, of which 177 were differentially expressed at six time points over a 24-h period. GO enrichment analysis revealed that genes at all time points were enriched in transport, carbohydrate, and lipid metabolic processes, and signaling pathways, particularly phytohormone signaling. In addition, co-expression network analysis revealed four modules strongly correlated with photoperiod. Within these four modules, 496 hub genes were identified with a high degree of connectivity to other photoperiod-sensitive DEGs, including two previously reported photoperiod- and temperature-sensitive genes affecting male fertility, Carbon Starved Anther and UDP-glucose pyrophosphorylase, respectively. This work provides a new understanding on photoperiod-sensitive pollen development in rice, and our gene expression data will provide a new, comprehensive resource to identify new environmentally sensitive genes regulating male fertility for use in crop improvement.